Public education through communication campaigns in increasing recycling participation - Sulaiman , Ahmad Riski; Usman, Ali; Ritonga, Torkis; Ruki, Taufik Rahman; Ibrahim, Ali; Hasibuan, Nurharisyah (Universitas Ahmad Dahlan, 2024)
In the modern era, environmental issues have become a global concern, with waste management emerging as a primary focus. This research aims to analyze the role of communication campaigns in public education, specifically to increase student participation in recycling activities. The study employs a Participatory Action Research (PAR) approach with a case study method to explore how communication campaigns can shape public awareness, attitudes, and behaviors towards recycling. The findings indicate that effective communication campaigns, which include the use of social media, direct outreach, and collaboration with local communities, can enhance students' understanding of the importance of recycling and motivate them to actively participate. Additionally, the research reveals that recycling participation increases when communication campaigns are tailored to the local context and involve active student participation. Therefore, this study concludes that public education through communication campaigns is a crucial strategy for increasing recycling participation and can contribute to environmental preservation, particularly at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. The implications of these findings suggest the need for more focused and sustainable communication campaigns to maximize the impact of public education on recycling participation.